UPAYA PENINGKATAN HASIL BELAJAR PJOK MELALUI METODE PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA SISWA KELAS XI F1 SMA NEGERI 7 BONE - Tri Ayu Astuti; Rijaluddin, Khalid; Mutmainna, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Physical Education, Sports, and Health (PJOK) learning requires active student involvement to achieve optimal learning outcomes. However, initial observations of Grade XI F1 students at SMA Negeri 7 Bone indicated that learning outcomes in volleyball underhand passing had not been optimal, as reflected in students’ limited participation and cooperation and the fact that not all students had achieved the Minimum Mastery Criteria (KKM). This study aimed to improve students’ PJOK learning outcomes in volleyball underhand passing through the implementation of the Jigsaw cooperative learning method. This study employed Classroom Action Research (CAR) with a descriptive quantitative approach based on the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection. The participants were 29 students of Grade XI F1 at SMA Negeri 7 Bone. Data were collected through learning achievement tests, practical performance assessments, and attitude observations. The results showed that students’ learning mastery increased from 66% in the pre-action stage to 86% in Cycle I. In Cycle II, all 29 students achieved the Minimum Mastery Criteria. Therefore, the implementation of the Jigsaw cooperative learning method can improve students’ PJOK learning outcomes in volleyball underhand passing.